Enhancing Indonesian Maritime Route Security to Prevent Transnational Crime - Daniel, Cherryl Gwyneth; Daniel, Christian Gerald; Marzaman, Atika Puspita (Poltanesa, 2023)
This paper highlights the transnational crime issues that have threatened Indonesia’s maritime security in recent years, then explores the possible challenges and how Indonesia has improved its response to these issues. Major acts that have affected Indonesia's maritime security include the Abu Sayyaf terrorist group, illegal actions by Vietnamese, Malaysian, and Singaporean fishermen, smuggling and human trafficking by Captain Bram, as well as drug trafficking that has developed during the COVID-19 pandemic. From the issue of illegal fishing only, Indonesia has suffered a loss of 477.33 million USD in 2014-2021. Many obstacles limit efforts to find solutions, a combination of internal factors such as Indonesia's lack of quality resources, and external factors such as maritime border disputes and the absence of clear definitions to assess maritime security conditions in various international cooperation. Our government has responded by initiating several national resource development plans, such as the establishment of Bakamla, implementation of presidential regulation no. 16 of 2017, developing infrastructures such as sea tolls and port renewal, as well as created cooperative relationships with various countries, namely Australia, the Philippines, Malaysia, China and other countries in the Southeast Asia and the Indian Ocean regions. Consequently, a trusting relationship with good communication can be formed between Indonesia and other countries to address threats to maritime security and reduce the number of transnational crimes in Indonesian waters, although not yet in large numbers.